ChemInform Abstract: Base‐Free Direct Synthesis of Alkynylphosphonates from Alkynes and H‐Phosphonates Catalyzed by Cu2O. Issue 29 (29th June 2016) - Moglie, Yanina; Mascaro, Evangelina; Gutierrez, Victoria; Alonso, Francisco; Radivoy, Gabriel
Abstract: The simple and mild protocol tolerates a wide variety of functional groups on the parent alkynes and can be run on gram scale.